2019
DOI: 10.1016/j.crfs.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cysteine addition and heat treatment on the properties and microstructure of a calcium-induced whey protein cold-set gel

Abstract: A model gel of whey protein isolate (WPI) was prepared by cold gelation with calcium. This system was modified by the addition of free cysteine residues (Cys) at different steps of the process. The WPI cold-set gels obtained were then subjected to heat treatment at 90°C. First, the effect of Cys addition on the heat-induced aggregation of WPI was studied through Atomic Force Microscopy (AFM) and infrared spectroscopy (ATR-FTIR), while Cys' effect on cold gelation was observed by AFM, Confocal Laser Scanning Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…The increase of random coil and ɑ‐helix proportions in protein can reflect the changes of Δ H (Liu et al, 2016). As can be shown in Table 3, there are an increase in the Δ H values of roasted and steamed walnut kernel compared to that of untreated sample, which suggested that the heating treatment could increase the unfolding molecular structure of protein and change the stable structure of protein (Lavoisier et al, 2019). The value of Δ H was the highest in roasting and steaming for 20 min, which was 7.07 and 8.69 J g −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The increase of random coil and ɑ‐helix proportions in protein can reflect the changes of Δ H (Liu et al, 2016). As can be shown in Table 3, there are an increase in the Δ H values of roasted and steamed walnut kernel compared to that of untreated sample, which suggested that the heating treatment could increase the unfolding molecular structure of protein and change the stable structure of protein (Lavoisier et al, 2019). The value of Δ H was the highest in roasting and steaming for 20 min, which was 7.07 and 8.69 J g −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Ovalbumin ist mit 386 Aminosäuren hinreichend lang und unterstützt mit Cystein eine Netzwerkbildung innerhalb von wenigen Minuten. [13,14] Dabei konkurriert Ovalbumin mit sich selbst: zum einen dienen dessen hydrophoben Sequenzen zur Emulsion, zum anderen werden Ovalbumine bei Temperaturen oberhalb 70 °C intermolekular vernetzt. Hydrophobe Sequenzen werden zugunsten der Vernetzung von der Öl-Wasser-Grenzfläche gelöst.…”
Section: Experimentelle Methoden Und Unterschiedeunclassified
“…1), which is typically observed when the structure of protein aggregate gels is broken. 48 The irreversible deformation of samples (=critical strain) occurred at γ ≈ 2.5% for WBD, and at γ between 0.5 and 1% for the three commercial products. These results show that the properties of WBD enriched in proteins and formulated mainly with whey proteins (WP : CAS ratio = 80 : 20) were comparable to the rheological properties of a stirred yogurt.…”
Section: Rheological Properties Of the Dairy Productsmentioning
confidence: 96%